Pengaruh Pajanan Sinar Matahari terhadap Penuaan Kulit Wajah Berdasarkan Penilaian Skin Analyzer pada Perempuan Minahasa di Sulawesi Utara (Medical Scope Journal, 2026)
Abstract: Sun exposure is considered the predominant extrinsic contributor to skin aging. This was an observational analytical study with a cross-sectional design involving 177 Minahasan women aged 30-69 years residing in Manado City, Tomohon City, and Minahasa Regency, North Sulawesi Province, Indonesia. Participants were categorized into low sun exposure group (≤2 hours per day; n = 82) and high sun exposure group (≥5 hours per day; n = 95), based on the average daily exposure over the past ten years. Demographic data and sun exposure status were obtained through interviews and structured questionnaires. Facial skin aging was assessed using a skin analyzer, evaluating pores, wrinkles, pigmentation, and facial sebum. The results demonstrated that, overall, participants with high sun exposure had higher scores for pores, wrinkles, pigmentation, and U-area sebum than those with low sun exposure (all p